2009
DOI: 10.1002/pssc.200881446
|View full text |Cite
|
Sign up to set email alerts
|

Is there an impact of threading dislocations on the characteristics of devices fabricated in strained‐Ge substrates?

Abstract: D. Placencia et al. report on the creation of organic photovoltaic cells from textured titanyl phthalocyanine (TiOPc) heterojunctions. The foreground of this frontispiece shows the crystal structures of the two polymorphs of TiOPc used, along with FE‐SEM images of TiOPc on an ITO electrode before (left), and after (right) phase transformation of the TiOPc film. The background shows AFM phase images of the two TiOPc polymorph films, showing the dewetting of the surface and the nanotexturing which occurs during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…6 illustrates that better electrical characteristics have been obtained for the highest pre-epi bake step. 7 This is true not only for the on-current ͑hole mobility͒, but also for the off-state current, where the drain-bulk leakage current of Fig. 6 is part of.…”
Section: R2mentioning
confidence: 95%
See 2 more Smart Citations
“…6 illustrates that better electrical characteristics have been obtained for the highest pre-epi bake step. 7 This is true not only for the on-current ͑hole mobility͒, but also for the off-state current, where the drain-bulk leakage current of Fig. 6 is part of.…”
Section: R2mentioning
confidence: 95%
“…4b͒ and is barely affected by annealing. 7 The strain in the as-grown s-Ge layers is in the range of 0.9%, as measured by high resolution X-ray diffraction ͑HR-XRD͒ ͑Fig. 5͒.…”
Section: Thin Strained Epitaxial Ge Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…This yields a value of a few 10 9 cm À 2 for a 100 nm epilayer. Previous investigations of Ge pMOSFET parameters have shown that a threading dislocation density in the range above 10 9 cm À 2 is required to affect the threshold voltage and the long-channel mobility [61,69], while as shown in Fig. 5, the drain-substrate diode leakage is sensitive to lower threading defect densities.…”
Section: Defect Aspects In Ge-on-si and Geoimentioning
confidence: 96%
“…5. This can be explained by the fact that in the first instance the diode leakage increases with the TDD [60,61]. In addition, it has been found that the one decade lower threading dislocation density in sGe layers also yields a lower excess GenerationRecombination (GR) noise in weak inversion transistor operation [62].…”
Section: Defect Aspects In Ge-on-si and Geoimentioning
confidence: 99%